The Significance of 18F-Fluorocholine-PET/CT as Localizing Imaging Technique in Patients with Primary Hyperparathyroidism and Negative Conventional Imaging - Fischli, Stefan; Suter-Widmer, Isabelle; Nguyen, Ba Tung; Müller, Werner; Metzger, Jürg; Strobel, Klaus; Grünig, Hannes; Henzen, Christoph (Frontiers in Endocrinology, 2018)
Objective The essential prerequisite for focused parathyroidectomy in patients with primary hyperparathyroidism (pHPT) is proper localization of all autonomic tissue. Sensitivity of conventional imaging modalities (ultrasound, 99mTc-sestamibi scintigraphy/SPECT/CT) is influenced by different factors (i.e., size/weight and position of autonomic tissue) and decreases in the presence of a multinodular goiter. Therefore, a considerable percentage of pHPT patients have negative or equivocal localization studies before surgery. The aim of this study is to evaluate the utility of FCH-PET/CT for preoperative localization in patients with pHPT and negative/equivocal 99mTc-sestamibi scintigraphy/SPECT/CT and/or ultrasound. Methods and measurements Between 2014 and 2017, a total of 39 patients with pHPT and negative/equivocal conventional imaging were referred for FCH-PET/CT. In the analysis, we included those (n = 23) who had surgery and a histopathologic workup of the lesions. Results 19 of 23 patients demonstrated no tracer uptake with 99mTc-sestamibi scintigraphy/SPECT/CT, 6 patients had an equivocal sonographic lesion, and multinodular goiter was present in 43% (10/23). In 21 of 23 patients, hyperfunctioning parathyroid tissue was identified correctly by FCH-PET/CT [21 true positive, 1 false negative, and 1 false positive; per-patient sensitivity 95.5% (95% confidence interval CI, 77.2–99.9)]. 29 lesions were resected [21 true positives, 3 false negatives, 1 false positive, and 4 true negatives; per-lesion sensitivity 87.5% (95% CI, 67.6–97.3)]. All patients were classified as having surgical success according to a decrease of intraoperative parathyroid hormone of ≥50% and normalization of postoperative serum calcium levels. Conclusion Despite a high prevalence of multinodular goiter, diagnostic accuracy of FCH-PET/CT in our patient group was excellent. Therefore, FCH-PET/CT is a promising new imaging tool in patients with pHPT and negative/equivocal results by conventional imaging techniques.